Vocational Education, Earnings and Job Satisfaction in Europe - Seamus McGuinness; Lorcan Kelly; Anne Devlin; Adele Whelan (Institute of Labor Economics (IZA), 2025)
This paper examines the earnings and job satisfaction of Vocational Education and Training (VET) graduates in the European Union (EU) using two definitions of vocational education: a self-reported definition and a more specific definition that incorporates work-based learning. The incidence of third-level VET falls from 74% to 29% under the stricter definition. Across the EU, the returns to vocational and academic qualifications are comparable for upper secondary, post-secondary and tertiary qualifications. Earnings premia vary between countries, with VET generating higher returns in just under one-third of all EU-28 members. Additionally, third level VET graduates enjoy higher levels of job satisfaction.
Keywords: I21; I26; J24; J30; J31; 330; vocational education; earnings; job satisfaction; european countries; work-based learning; on-the-job training